2020
DOI: 10.3390/s20102817
|View full text |Cite
|
Sign up to set email alerts
|

Potentiometric Solid-Contact Ion-Selective Electrode for Determination of Thiocyanate in Human Saliva

Abstract: A new solid-contact potentiometric ion-selective electrode for the determination of SCN− (SCN-ISE) has been described. Synthesized phosphonium derivative of calix[4]arene was used as a charged ionophore. The research included selection of the ion-selective membrane composition, determination of the ISEs metrological parameters and SCN-ISE application for thiocyanate determination in human saliva. Preparation of the ISEs included selection of a plasticizer for the ion-selective membrane composition and type of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 84 publications
0
4
0
Order By: Relevance
“…Similarly, ISEs have been used for the detection of salivary thiocyanate. Urbanowicz et al (2020) demonstrated a new solid-contact potentiometric ISE for determining thiocyanate levels in human saliva. Researchers used a synthesized phosphonium derivative of calix[4] arene as a charged ionophore and found the most advantageous parameters when using glassy carbon sensors as the electrode material.…”
Section: Electrochemical Techniquesmentioning
confidence: 99%
“…Similarly, ISEs have been used for the detection of salivary thiocyanate. Urbanowicz et al (2020) demonstrated a new solid-contact potentiometric ISE for determining thiocyanate levels in human saliva. Researchers used a synthesized phosphonium derivative of calix[4] arene as a charged ionophore and found the most advantageous parameters when using glassy carbon sensors as the electrode material.…”
Section: Electrochemical Techniquesmentioning
confidence: 99%
“…The electrode had a wid range of 0.5-12.5 and a good detection limit of 5.6 × 10 −6 M. The ISE was also characte by an average slope and linearity range. Urbanowicz et al presented three types of SCN − -ISEs, where one was a liqui two were solid contact electrodes [100]. All three electrodes in the membrane had ionophore a tetrakis-(4-diphenylmethylphosphonium-butoxy)-tetrakis-p-tert-buty [4]arene tetrathiocyanate (Figure 25).…”
Section: Ion-selective Electrodes Sensitive To Tiocyanate Ionsmentioning
confidence: 99%
“…Analogous to the electrode describ the previous paper, the concentration of SCN − ions in the saliva of non-smokers and s ers was investigated. Urbanowicz et al presented three types of SCN − -ISEs, where one was a liquid and two were solid contact electrodes [100]. All three electrodes in the membrane had as an ionophore a tetrakis-(4-diphenylmethylphosphonium-butoxy)-tetrakis-p-tert-butylcalix [4]arene tetrathiocyanate (Figure 25).…”
Section: Ion-selective Electrodes Sensitive To Tiocyanate Ionsmentioning
confidence: 99%
“…Contrarily, potentiometric sensors are commonly used for urea determination in biological and environmental samples [8][9][10]. Direct potentiometric sensing with minimal sample pre-treatment and fast and reliable data processing is the method-of-choice in medical laboratories for determination of many diagnostically important analytes, for example, Na + , K + , Ca 2+ , H + , Cl − , and SCN − [10][11][12][13][14]. Enzyme immobilization on the surface of the ion-selective membrane enables detecting and determining the non-ionic analytes, such as urea, by detecting changes in the concentration of ionic products of enzymatic reactions.…”
Section: Introductionmentioning
confidence: 99%